Revision zweier europäischer Drosophila-Arten. - Herting, Benno Wilhelm (Contributions to Entomology = Beiträge zur Entomologie, 1953)
Nomenclatural Actsguyenoti Burla, 1948 (Drosophila), syn. n. of Drosophila deflexa Duda, 1924nitens Buzzati, 1943 (Drosophila), syn. n. of Drosophila rufifrons Loew, 1873